P024: Obtaining consensus on optimal management and follow-up of patients presenting to the emergency department with early pregnancy complications – a modified Delphi study. (May 2019) - Cornelis, A.; Clouston, R.; Atkinson, P.
Abstract : Introduction : Complications in early pregnancy are common and have many physical and emotional consequences. Locally, there is no early pregnancy loss clinic or standardized guide in the emergency department (ED) for referral and follow-up decisions, and both initial management of patients and follow up can be inconsistent. This study aimed to obtain consensus on the best approach to initial work-up, management, and follow up for patients who present to the ED with early pregnancy complications, with the goal of using this consensus to produce a standardized guide for emergency provider use.Methods : A literature review was completed to produce evidence-based recommendations which were used to initiate a modified Delphi consensus process. A survey was distributed, with three rounds completed. Participants included emergency providers, obstetrician-gynecologists, a radiologist, a sample of family medicine physicians including some involved in primary care obstetrics, and nurse practitioners. An obstetric specialist from outside the local region was also involved.Results : Consensus was reached on several key recommendations, however some areas remained without clear accepted best practice. There was consensus that physical components of early pregnancy complications are addressed well, but that we could improve on patient flow and more consistent follow up. Important investigations to be done for patients were identified. The timing of formal ultrasound, necessity and timing of obstetrician consultation, and safety of discharge was addressed for various patient scenarios including stable and unstable patients, with and without adnexal pain, with intrauterine pregnancy of uncertain viability, and with pregnancy of unknown location. Management of confirmed early pregnancy loss in the ED and family medicine clinics was addressed. Barriers to an early pregnancy loss clinic included lack of funding, space, and staffing as well as lack of resources and uncertain patient volumes. A feasible alternative to an early pregnancy loss clinic was for willing providers to keep appointment times available to facilitate confirmation of follow-up prior to discharge. Other suggested alternatives included an early pregnancy loss clinic, a nurse educator, and having a standardized guideline in the ED.Conclusion : Through a consensus approach, several recommendations were agreed upon for improving care for patients presenting to the ED with early pregnancy complications.